The Influence of Ecotheological Value Internalization on Green Organizational Behavior: an Empirical Study of Civil Servants at the Ministry of Religious Affairs, Palembang City - Budiman; Baharudin (CV. Era Digital Nusantara, 2026)
The global ecological crisis demands organizational behavior transformation in the public sector, particularly in religious institutions like Indonesia's Ministry of Religious Affairs (Kemenag), which hold strong moral legitimacy in society. This study examines the influence of ecotheological value internalization (INE) encompassing ecological-spiritual identity, transcendental meaning in bureaucracy, collective stewardship commitment, and ethical ecological decision-making on green organizational behavior (GOCB/POH), namely voluntary actions such as eco-initiatives, green advocacy, and interpersonal eco-helping. Employing an explanatory quantitative design, the research surveyed 385 civil servants (ASN) at the Palembang City Kemenag Office via proportionate stratified random sampling, using validated Likert-scale questionnaires (Cronbach's α = 0.85–0.92). Simple linear regression analysis with IBM SPSS version 32 revealed a positive and significant effect of INE on GOCB (R = 0.507; R² = 0.257; β = 0.519; t = 11.51; p < 0.001), explaining 25.7% of GOCB variance. These findings reinforce the Value-Belief-Norm (VBN) theory and workplace ecospirituality adaptation in Islamic religious bureaucracy contexts, with practical implications for integrating INE into Kemenag's vision-mission to accelerate green bureaucracy aligned with SDGs and Asta Protas. The cross-sectional design's limitations suggest future longitudinal research.